KEBIJAKAN TRANSFORMASI SUMBER DAYA MANUSIA PADA SEKOLAH MENENGAH KEJURUAN DI KABUPATEN SITUBONDO (STUDI KASUS SMKN 1 SITUBONDO) (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2013)
The concept is based transformative education that will give you change in the public education of the community developed into a modern society based on knowledge and technology. This study aims to determine the transformation of human resource policies on Vocational High School 1 Situbondo. The study sample is key informants selected through a process of observation by purposive sampling method is performed on a component policy makers at Vocational High School 1 Situbondo by 11 people. This study used a qualitative approach through in-depth interviews, documentation and observation. Analysis using analytical methods deksriptis Spradley (1997) ethnographic model which includes domain analysis, taxonomic, and analysis komponensial kultutal.Pola theme of leadership in educational efforts menngah kejuruaan can be developed through transformational and charismatic leadership backed by political power, business networks and bureaucratic network. In reality, the pattern of leadership is also based on commitment, exemplary leadership and courage in taking a risk on each policy will be implemented. Leaders always puts the entrepreneurial spirit in the leadership pattern and process of teaching the students the students to produce human resources who are competent and capable of creating jobs.